The Concept of an Epilepsy Brain Bank - Hernandez-Ronquillo, Lizbeth; Miranzadeh Mahabadi, Hajar; Moien-Afshari, Farzad; Wu, Adam; Auer, Roland; Zherebitskiy, Viktor; Borowsky, Ron; Mickleborough, Marla; Huntsman, Richard; Vrbancic, Mirna; Cayabyab, Francisco S.; Taghibiglou, Changiz; et al. (Frontiers in Neurology, 2020)
Epilepsy comprises more than 40 clinical syndromes affecting millions of patients and families worldwide. To decode the molecular and pathological framework of epilepsy researchers, need reliable human epilepsy and control brain samples. Brain bank organizations collecting and supplying well-documented clinically and pathophysiologically tissue specimens are important for high-quality neurophysiology and neuropharmacology studies for epilepsy and other neurological diseases. New development in molecular mechanism and new treatment methods for neurological disorders have evoked increased demands for human brain tissue. An epilepsy brain bank is a storage source for both the frozen samples as well as the formaldehyde fixed paraffin embedded (FFPE) tissue from epilepsy surgery resections. In 2014, the University of Saskatchewan have started collecting human epilepsy brain tissues for the first time in Canada. This review highlights the necessity and importance of Epilepsy Brain bank that provides unique access for research to valuable source of brain tissue and blood samples from epilepsy patients.